2018
DOI: 10.1186/s41479-018-0049-2
|View full text |Cite
|
Sign up to set email alerts
|

Rapid molecular assays for detection of tuberculosis

Abstract: Tuberculosis (TB) is an infectious disease that remains an important public health problem at the global level. It is one of the main causes of morbidity and mortality, due to the emergence of antibiotic resistant Mycobacterium strains and HIV co-infection. Over the past decade, important progress has been made for better control of the disease. While microscopy and culture continue to be indispensible for laboratory diagnosis of tuberculosis, the range of several molecular diagnostic tests, including the nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 94 publications
(118 reference statements)
0
41
0
Order By: Relevance
“…Notwithstanding the fact that genotypic drug susceptibility testing has a high sensitivity and specificity but is still unable to detect all the resistance, especially in strains with novel or unknown resistance mechanisms [ 40 , 41 ]. In this review, 49 isolates with confirmed phenotypic RIF-resistance do not harbor any known mutation in the rpoB gene, which may be explained by the fact that RIF resistance-conferring mutations are present elsewhere in the rpoB gene (such as a V146F and I572F) [ 42 , 43 ], suggesting that the nature and frequency of mutations in the rpoB gene vary considerably, between different geographical regions [ 44 ], by the fact that not all the mutations are targeted by the probes used [ 45 ], or as it has been reported that molecular assays still have some drawbacks, such as product cross contamination which is a major problem leading to false positive results [ 20 ]. The reason for this cross contamination has not been elucidated properly [ 46 ], but it may be due to laboratory procedures (protocol for pretreatment, DNA extraction, and detection of the amplification product) [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notwithstanding the fact that genotypic drug susceptibility testing has a high sensitivity and specificity but is still unable to detect all the resistance, especially in strains with novel or unknown resistance mechanisms [ 40 , 41 ]. In this review, 49 isolates with confirmed phenotypic RIF-resistance do not harbor any known mutation in the rpoB gene, which may be explained by the fact that RIF resistance-conferring mutations are present elsewhere in the rpoB gene (such as a V146F and I572F) [ 42 , 43 ], suggesting that the nature and frequency of mutations in the rpoB gene vary considerably, between different geographical regions [ 44 ], by the fact that not all the mutations are targeted by the probes used [ 45 ], or as it has been reported that molecular assays still have some drawbacks, such as product cross contamination which is a major problem leading to false positive results [ 20 ]. The reason for this cross contamination has not been elucidated properly [ 46 ], but it may be due to laboratory procedures (protocol for pretreatment, DNA extraction, and detection of the amplification product) [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Drug susceptibility testing (DST) induces serious delays in the detection of resistance due to the extremely slow growth of MTB (takes several weeks to months) [ 19 ]. To overcome the limitations of phenotypic methods, various molecular detection methods have been recommended and endorsed by the WHO [ 20 ]. These methods can speed up MBT identification and drug susceptibility testing, and thus lead to faster and more specific treatment of patients [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Line probe assays use reverse hybridization methods to detect resistant variants to first-and second-line antibiotics. These methods are fast, reliable and accurately predict resistance in 88-95% of the cases for rifampicin, 91% for isoniazid and 86-100% for second-line antibiotics (16). However, they are necessarily constrained to specific sets of mutations and thus lack flexibility.…”
Section: Wgs For Resistance Diagnostics a Use Of Mutations As Resistmentioning
confidence: 99%
“…Tuberculosis (TB) is the most lethal infectious disease caused by a single agent, namely bacteria belonging to the Mycobacterium tuberculosis complex (MTBC)[1]. Whereas isolating the bacteria from clinical specimens is a time-consuming process that delays both clinical diagnosis and research workflows, rapid molecular tests have the potential to identify the pathogen DNA in a few hours [2,3]. This is the main reason why the development of new molecular tools for TB diagnosis is an active area of research, with many companies involved, looking for the endorsement of the World Health Organization (WHO) [4].…”
Section: Introductionmentioning
confidence: 99%